An Exploration of Artistic and Technological Symmetry (LEARNing Landscapes, 2018)
In this interview, biologist, artist, and shiatsu healer Artemis Papert describes how computational thinking can help people organize their thoughts in a more formal way. She discusses TurtleArt, a software that allows both children and adults to create two-dimensional static art images using geometry and coding as a medium. TurtleArt not only bridges the worlds of math and art, but is also easy to learn. She concludes by reading an excerpt from the article, “Teaching Children Thinking”— written in 1971 by her father Seymour Papert—as a still relevant starting point for where technology is heading.
Keywords: TurtleArt; computational thinking and children; powerful learning and technology